A experiência do “tornar-se mãe” em mães biológicas e em mães adotivas - Casarotto, Mariana (Universidade Federal de São Carlos, 2021)
For many years motherhood was a prerequisite for women to have space in societies. This condition carried with it an ambivalence, as women gained social recognition, but needed to renounce their personal desires and aspirations in the name of motherhood. Elements based on the feminist movement openednew perspectives for women's lives, as well as new possibilities for the experience of motherhood: adoption being one of them . Given that there are different motivations and ways which lead women to become mothers, it is important to understand the psychological aspects involved in this stage of these women's lives, experienced more strongly by first time mothers. The aim of the study is to evaluate psychological variables of biological and adoptive primiparous mothers during the first four months of contact with their child, in order to identify similarities and differences in the processes of becoming a mother. From a multiple-case study design, two biological primiparous mothers and two adoptive primiparous mothers, who were in the first four months of living with their child, were recruited. The mothers answered the Social Support Perception Scale (EPSUS-A), and over the period of four months completed the monthly semi-structured assessment guide and built an online experience diary The qualitative study of data obtained was done through a thematic analysis, using the Atlas.ti software. The quantitative data were analyzed through descriptive analysis and differences between different periods of data collection was analyzed by Wilcoxon test. Similarities and differences were found in the participants processes of becoming a mother. Similarities included the existence support network, feelings in general, the importance of the baby's development to build the relationship of the dyad and the impact of the COVID-19 pandemic on the mother. The differences were in relation to body changes on biological mothers, breastfeeding, and a greater perception of a support network of biological mothers when compared to adoptive mothers, who, in turn, experienced the psychological aspects related to the process of waiting for legal adoption. Thus, the study discusses that the experience of motherhood is a unique event for each woman and her experience is related to each woman's individual process, and a support network contributes throughout this process.
The experience of "becoming a mother" in biological and adoptive mothers
Keywords: maternidade; adoção; gravidez; aspectos psicológicos; psicologia perinatal; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA